Conceptual Lanchester-type Decapitation Warfare Modelling - Menq, Jau-yeu; Tuan, Pan-chio; Liu, Ta-sheng (Defence Science Journal, 2007)
Decapitation operation has existed for a long time in military history; however, it was notuntil March 2003 'decapitation attack' became a well known term in the mass media. This paperis based on the connotation of decapitation based on historical study and refines the term intomilitary strategic concept of decapitation strategy. Ideas derived from detailed studies onLanchester-type combat models are used to describe the effectiveness of conventional regularforces under decapitation warfare, which includes asymmetric, nonlinear, stand-off and specialoperation forces (SOF) operations. A conceptual model is presented to describe the effects ofthe decapitation strategy on the regular battlefield. With extensive coverage of operational factorssuch as robustness of forces, time difference between combats, undermining effects, breakpoints,attrition rates, total force level and force allocation, the model is suitable to analyse complexscenario with different types of military operations consisting of decapitation strategy. Anillustrative example is provided to demonstrate the application of the model. The conceptualmodel is built based on hypotheses, assumptions, and criteria. In the absence of historical data,no data analysis and parameter estimation are involved.